Population dynamics of the mullet fish, Rhinomugil corsula (Hamilton, 1822), in the Sitakunda coast of the Bay of Bengal (Bangladesh Journal of Zoology, 2019)
Population dynamics of the mullet species, Rhinomugil corsula, was studied, using FiSAT-II program, with the length-frequency data of 2480 fish specimens. The asymptotic length (L∞) and growth coefficient (K) of this fish were estimated to be 31.4 cm and 1.0/year, respectively. The instantaneous rate of natural mortality (M), fishing mortality (F) and total mortality (Z) were estimated to be 1.73, 1.20 and 2.93, respectively. The recruitment pattern of the species was prolonged with two peaks, major peak during June to December and a minor peak during January to April. The L25, L50 and L75 were found to be 8.61, 10.42 and 12.23 cm, respectively. The relative yield per recruit (Yʹ/R) and biomass per recruit (Bʹ/R) were 0.751 and 1.731, respectively. The value of exploitation (E) was found to be 0.41 which indicated that R. corsula was not over fished (E > 0.50) in the study area. The maximum exploitation (Emax) value was 0.55. The growth performance index (ϕ´ = 2.99) of R. corsula in the Sitakunda coast of the Bay of Bengal was found to be moderate.Bangladesh J. Zool. 47(2): 305-314, 2019